Inclusão das representações de gary e de skilling-umoto em modelos de linhas de transmissão trifásicas: Aplicação em simulações de transitórios eletromagnéticos em sistemas de energia elétrica - Silva, Rodrigo Cleber da [UNESP] (2015)
In this project will be developed a model for three-phase transmission line that may be included in the corona effect. The model will be developed directly in the time domain and the same is based on the hypothesis that a short segment of three phase line can be represented by a circuit constituted by discrete elements (resistance, inductance, capacitance, and conductance). The insertion of the corona effect in the line model will be based on Gary and Skilling-Umoto models that, until the present time, is used to insert the corona effect in models of transmission lines monophasic. The model to be developed can be utilized to represent generic three-phase lines, regardless of the line geometry, in electromagnetic transient simulations that can occur in electrical power systems. The great contribution that will result from the development of this project will be the making available of a model line more complete than the currently available models, since the proposed model can be applied to any three-phase line, regardless of the geometry of the line, and will take into consideration the corona effect (which is responsible for distortions in the waveforms of voltages and currents that propagate along the line during the occurrence of disturbance). A more accurate model line that provides for such distortions may be useful in the analysis of the protection system, allowing for a more precise fit and increasing the reliability of the electric power system